Examining the effects of anxiety and education level on mental health: The role of spiritual intelligence as an intervening variable in post COVID-19 patients in Indonesia [version 4; peer review: 1 approved, 2 approved with reservations] - Yuly Peristiowati; Sentot Imam; Ahmad Yunus; Anis Ansyori (F1000Research)
Background The COVID-19 pandemic has profoundly affected global health systems and daily life, exacerbating vulnerabilities, particularly in Indonesia. This study investigates the impact of anxiety and education level on mental health, with spiritual intelligence as an intervening variable among post-COVID-19 patients in Indonesia. Methods Utilizing a cross-sectional design, data were collected from 390 post-COVID-19 patients in Indonesia. Structured questionnaires assessed anxiety, education level, spiritual intelligence, and mental health. Structural Equation Modeling (SEM) was used to analyze the relationships among these variables. Results The findings indicate that anxiety significantly affects both spiritual intelligence and mental health, with spiritual intelligence acting as a mediating factor. Additionally, higher educational attainment is positively associated with enhanced spiritual intelligence and improved mental health outcomes. Conclusions The study underscores the importance of incorporating spiritual development practices into mental health interventions and educational programs to boost resilience and overall well-being in the post-pandemic era. While these findings are promising, the cross-sectional design limits causal inferences, and future research should consider longitudinal studies to examine these relationships over time. These practices can help mitigate the adverse effects of anxiety and educational disparities on mental health.